FENOMENA FLYPAPER EFFECT PADA PENGELUARAN PEMERINTAH DAERAH FUNGSI PENDIDIKAN DI INDONESIA - Yolanda Wilda Artati; Ribut Nurul Tri Wahyuni (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2016)
Implementasi of regional autonomy and fiscal decentralization since 2001, have changed the pattern of education management from central government to local governments. In addtion, local governments are also required to alocate education budget about 20 percent of the total budget. Diffrences of potential areas will lead local goovernments to depend on transfers of funds from central government to reach the target of 20 percent of the total budget. It indicates flypaper effect of education spending of local governments in indonesia . This study identifyes flypaper effect of education spending of local governments by using spatial panel data model in 2011-2014. The result shows that elasticity of uncoditional grant is higher than local revenue , it can be interpeted that there is flypaper effect of education spending of local governments in Indonesia for resolving flypaper effect, local goverments can apply intensification and extensification of tax to increase of local revenue.